The Way of the Increasing Two Times the Efficiency of Silicon Solar Cell - Gulomov, Jasurbek; Aliev, Rayimjon (Physics and Chemistry of Solid State, 2021)
Increase of the efficiency of the solar cells which are produced in industry, is important. Increase of efficiency of solar cells was identified, when nanoplasmonics phenomenon was formed in solar cell. So, in this article, influence of nanoparticles Pt, Au, Ag and Cu on properties of silicon based solar cell has been studied. When nanoparticle Pt was inclused in silicon based solar cell, its efficiency increased 2.31 times. Optimal radius of nanoparticule Pt was identified to be between 15-25 nm.